2010
DOI: 10.1016/j.labeco.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Nepotism, incentives and the academic success of college students

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…However, the research carried out in Turkey has shown that age mattered to friends' patronage in the working environment [65]. Several studies in different activity areas and different countries confirm the trend that the support of the loved ones is often received at the start of a career [66,67], although support-related expectations may negatively affect the efforts of children themselves [68]. The results of another study conducted in Italy have demonstrated that children with kinship connections in an academic setting did not yield to those without such connections in their academic performance, although the existence of nepotism was not denied [69].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the research carried out in Turkey has shown that age mattered to friends' patronage in the working environment [65]. Several studies in different activity areas and different countries confirm the trend that the support of the loved ones is often received at the start of a career [66,67], although support-related expectations may negatively affect the efforts of children themselves [68]. The results of another study conducted in Italy have demonstrated that children with kinship connections in an academic setting did not yield to those without such connections in their academic performance, although the existence of nepotism was not denied [69].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, family owned firms tend to select dynastic management, also if there are no professional competencies and abilities internal to the family. This situation may generate, on average, lower quality of employers' human capital (Gevrek and Gevrek ) and conflicts of interests among members of a family owner, with negative consequences for managerial practices and organization of internal labour markets (Bloom et al ). If risk aversion, nepotism and rent seeking behaviour prevail in managerial activities, the influence of employers' education may be, ceteris paribus , neutralized in family firms compared to their non‐family counterparts.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…However, on the one hand, the quality of the training institution is linked to the cost of training, and, on the other hand, the cost of training children depends, in part, on the parents" level of income and, therefore, on their employment status. Second, Gevrek and Gevrek (2010) argue that parents" employment status influences self-employment. These authors argue that youths born to working parents, especially those who are self-employed, receive the resources (e.g., domain-specific skills, relationship networks, etc.)…”
Section: Father/mother Statusmentioning
confidence: 99%